The problem of justice and approaches to its solution - Vilenta, Inna (Actual Problems of Mind, 2017)
The article substantiates the relevance of the problem of studying discourses of justice, which will make possible to substantiate the procedures of an equitable social organization, as well as possible solutions of this problem, an important place of which is the modern communicative philosophy.